Evaluation of Antibiotic use with the ATC/DDD Method and DU 90% on Respiratory Tract Infection Patients - Sari, Nawang Wulan Nago Pita; Imba, Farhan; Risna, Risna; Litaay, Gabriela Welma (Indonesian Journal of Global Health Research, 2025)
Drug availability is one of the factors in the success of pharmaceutical services at the community health center (Puskesmas) as a Primary Health Facility (FKTP). The aim of this study was to determine the quantity of antibiotic use using the ATC/DDD method and DU 90%, as well as the percentage of antibiotic prescription conformity with the National Formulary (Fornas). The method used was an observational cross-sectional study with a descriptive approach. Data were collected retrospectively for the period of May to October 2024 at Khomba Health Center, Jayapura Regency. The results of this study indicate that the most commonly used antibiotic was Amoxicillin with a value of (1996.36 DDD/1,000/year). The antibiotic included in the DU 90% segment was Amoxicillin, and the level of prescription conformity with the National Formulary (Fornas) reached 100%.